Nexus between Fintech Adoptability and Customer’s Perception towards Fintech in the Islamic Banking Industry - Qureshi, Ahmed Mehmood; Rehman, Faisal; Khan, Muhammad Kamran; Khan, Amir (Pakistan Journal of Humanities and Social Sciences, 2023)
The prime motive of the study is to investigate the relation between customers' perceptions towards FinTech and its capacity to be adopted in Pakistan's Islamic banking industry. Additionally, it looks into how open customers are to embracing and using FinTech services in the Islamic banking industry. In order to full fil the motive of study, the primary data was collected from 385 clients of five Islamic banks operating in District Haripur, Pakistan. Structural equation modeling (SEM) and partial least square path modeling were used to analyze the data and test the hypotheses. Study found that customers' perceptions of FinTech adoption are strongly influenced by value earned, usefulness, safety, trust, and ease of use, whereas risk has only a little impact. Study recommends that Islamic banks need to strengthen FinTech to boost customer trust. Study also provide insights to decision makers and regulators in Islamic banking industry to ensure the provision of sound FinTech for its customers.